Geospatial Based Application for Dam Planning and Monitoring in Malaysia: A Review - Deros S.N.M.; Jalal K.A.; Ishak N.A.; Din N.M.; Naim M.R. (Springer Science and Business Media Deutschland GmbH, 2024)
Malaysia is well endowed with abundance of natural water resources, which has significantly contributed to the socio-economic development of the country. There are many catchment areas in Peninsular Malaysia and eastern Malaysia that can be used for water storage as dams and reservoirs. The monitoring of dams and reservoirs is important to observe the impact of aging, land use changes, ground movements and many more. The advancement of dam monitoring involved the usage of geospatial technology such as satellite imagery data and Geographic Information System (GIS). The study reviewed in this paper includes the change detection pattern of land use and land cover (LULC), its influence on sediment yield and soil erosion. Soil erosion and sedimentation are the major issues related to dams and reservoirs because it will deteriorate water quality and reduce reservoir capacity. In this paper, the review on different sensors and imagery used with the methods of interpretation are also analyzed. As a conclusion, satellite remote sensing applications highly contributes to the future developments of geospatial technology. This is enhanced by the evolution of algorithms and models that will induce efficient monitoring at a wider coverage area. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.